Transcriptome Dynamics of Double Recessive Mutant, o2o2o16o16, Reveals the Transcriptional Mechanisms in the Increase of Its Lysine and Tryptophan Content in Maize - Wang, Wei; Dai, Yi; Wang, Mingchun; Yang, Wenpeng; Zhao, Degang (Genes, 2019)
In maize, pyramiding of o2 and o16 alleles can greatly improve the nutritional quality of grains. To dissect its molecular mechanism, we created a double recessive mutant line, o2o2o16o16, by introgression of the o2 and o16 alleles into the wild-type maize inbred line, by molecular marker-assisted backcross selection. The kernels (18 day after pollination (DAP), 28 DAP, and 38 DAP) of the o2o2o16o16 mutant and its parent lines were subject to RNA sequencing (RNA-Seq). The RNA-Seq analysis revealed that 59 differentially expressed genes (DEGs) were involved in lysine metabolism and 43 DEGs were involved in tryptophan metabolism. Among them, the genes encoding AK, ASADH, and Dap-F in the lysine synthesis pathway were upregulated at different stages of endosperm development, promoting the synthesis of lysine. Meanwhile, the genes encoding LKR/SDH and L-PO in the lysine degradation pathway were downregulated, inhibiting the degradation of lysine. Moreover, the genes encoding TAA and YUC in the tryptophan metabolic pathway were downregulated, restraining the degradation of tryptophan. Thus, pyramiding o2 and o16 alleles could increase the lysine and tryptophan content in maize. These above results would help to uncover the molecular mechanisms involved in the increase in lysine and the tryptophan content, through the introgression of o2 and o16 alleles into the wild-type maize.